NEW INSIGHTS INTO THE CHEMISTRY OF OXOVANADIUM(IV) AND ZIRCONIUM (IV) COMPLEXES WITH TRIDENTATE COORDINATING LIGAND - K. ARUNA; SAKINA .Z. BOOTWALA; MOBASHSHERA TARIQ; CHRISTOPHER FERNANDES (International Journal of Pharma and Bio Sciences, 2014)
New Oxovanadium(IV) and zirconium (IV) complexes were synthesized with tridentate ligand and characterized by elemental analysis, molar conductance measurements, molecular weight determinations, IR, electronic, and 1H NMR studies. The Oxovanadium(IV) complex is non-electrolyte whereas zirconium(IV) complex is 1:2 electrolytes in nature and may be formulated as[(VOL)2SO4] and [ZrL2]Cl2 respectively, where L = ethyl 2-[(2E,3Z)-4-hydroxypent-3-en-2-ylidene]amino-4,5,6,7-tetrahydro-1-benzothiophene-3-carboxylate. The analytical data showed that the Schiff base ligand acts as tridentate toward metal ions via the azomethine nitrogen, ester carbonyl and enolic oxygen atom. Spectral studies and magnetic susceptibility measurement reveals square pyramidal geometry for VO (IV) and octahedral structure for Zr (IV) complex. These metal complexes also exhibited antibacterial activity against pathogenic strains causing urinary tract infections.